STASIUN RISET BEKANTAN PADA LAHAN BASAH - Melati, Aisyah; Muchamad, Bani Noor (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2021)
Wetlands are a natural habitat for endemic animals of South Kalimantan, namely proboscis monkeys (Nasalis larvatus). These primates are one indicator in wetlands conservation, but now the status of proboscis monkeys is endangered which means wetlands are naturally also damaged. This makes The Indonesian Proboscis Monkey Friends Foundation worried about the preservation of these primates who are endangered in a side the number of foreign researchers who are interested in proboscis monkeys so it also weakens status proboscis monkeys as endemic animals.The Indonesian Proboscis Monkey Friends Foundation wants the proboscis monkey in South Kalimantan to become an identity in the area along with the wetland ecosystem which is the habitat of proboscis monkeys. Therefore a fundamental problem with the design of the Proboscis Monkey Research Station on Wetlands is how the design of the proboscis research station on wetlands is in harmony with natural conditions around it so that it can become the identity of the region. Settlement the problem was solved through the metabolism-organic method and the visual identity-metaphor method. The metabolism-organic method is the solution to the problem of harmony building with nature, while the visual identity-metaphor method is the solution in the matter of regional identity. Based on the two methods, the concept proposed for this design is the concept of "subject-object interaction" which is realized through the concept of "wetland ecology". This concept of "subject-object interaction and wetland ecology" is a concept that elevates interactions between researchers and wetland organisms such as proboscis monkeys by entering the wetland elements into the design of this research station.